The Proposed EPA Plant Pesticide Rule - Nester, Eugene W.; Brakke, Myron K.; Chilton, Marydell; Fedoroff, Nina V.; Kelman, Arthur (Council for Agricultural Science and Technology (CAST), 1998)
A panel of five members of the National Academy of Sciences formed by CAST examine the scientific merits of the Biotechnology Industry Organization response to the major conclusions reached by eleven professional scientific societies on the U.S. Environmental Protection Agency proposal to regulate genes which make plants resistant to pests by means of genetic engineering under the same regulations developed for use of chemical pesticides applied to plants.
Keywords: EPA; Plant Pesticde; Biotechnology; NAS